25x-7-14x+2=23x-4-12x+17

Simple and best practice solution for 25x-7-14x+2=23x-4-12x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25x-7-14x+2=23x-4-12x+17 equation:


Simplifying
25x + -7 + -14x + 2 = 23x + -4 + -12x + 17

Reorder the terms:
-7 + 2 + 25x + -14x = 23x + -4 + -12x + 17

Combine like terms: -7 + 2 = -5
-5 + 25x + -14x = 23x + -4 + -12x + 17

Combine like terms: 25x + -14x = 11x
-5 + 11x = 23x + -4 + -12x + 17

Reorder the terms:
-5 + 11x = -4 + 17 + 23x + -12x

Combine like terms: -4 + 17 = 13
-5 + 11x = 13 + 23x + -12x

Combine like terms: 23x + -12x = 11x
-5 + 11x = 13 + 11x

Add '-11x' to each side of the equation.
-5 + 11x + -11x = 13 + 11x + -11x

Combine like terms: 11x + -11x = 0
-5 + 0 = 13 + 11x + -11x
-5 = 13 + 11x + -11x

Combine like terms: 11x + -11x = 0
-5 = 13 + 0
-5 = 13

Solving
-5 = 13

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 0=0.5x-7 | | -20.4=b+-4.6 | | -14.25+v=-21.55 | | 6x^2-30x+6= | | (4a-3)=(2a+9) | | -12.3=n-24.5 | | (5y-3)=22 | | s*5+36=106 | | 2x^2+1ox-48= | | 10h-28=72 | | 69-13=35 | | 5x-12=x+11 | | 2x+11-5x-13= | | -7.8q+1.6=-62.4-1.4q | | 3x+6y-330=0 | | (2p^6s^8)(s^8)= | | 27.7=20.2+b | | 7/12÷3/4 | | 15x^2+2x-24= | | (7x^2)(-4x^3)(6x^6)= | | N+-10.8=-35.4 | | s*6-28=55 | | x/300=12 | | 0.5x*0.2x=0.125 | | 3/4x5/6= | | (2x+5)=(6x+10) | | 6x^3=-22x+28x^2 | | -21.263+n=-44.464 | | Y-6=43 | | 6y-22=20 | | Logx=-3/2 | | 4f-8=16 |

Equations solver categories